New Approach on Planning for Water Provision using Water Balance (Case Study: Sewakaderma Municipal Waterworks, Denpasar) - Rahman, Herawati Zetha (Fakultas Teknik Universitas Pancasila, 2024)
The rapid growth of urban populations has led to an increase in water demand. Moreover, Public Water Supply Companies need to deal with water loss. This issue is primarily caused by aging water networks and poor infrastructure due to a lack of maintenance, which makes the piping system susceptible to damage and leakage. In Denpasar City, the pipeline network, which spans over 94,753 meters, is more than 40 years old. Given the current circumstances, in 2023 the amount of unaccounted water loss due to leakage reach 38%. This high percentage of Non-Revenue Water (NRW) has several negative consequences, including a decrease in the quality of distributed water, a reduction in PDAM profits, and limitations on the city government's ability to expand and achieve 100% coverage. The objective of this study is to estimate the potential demand and supply of PDAM Denpasar City. Using Quantitative and qualitative approach, with minimum water demand of 129.46 liters per person per day (lpd). The Water Supply Simulation of Denpasar City reveals that to achieve optimal conditions, PDAM Denpasar City must reduce NRW from 38% to 19.5% by 2044. This can be accomplished through various measures, including the replacement of the Primary Distribution Network along 116.95 kilometers, replacement of 51.03 kilometers Secondary Distribution Network, the installation of 78 District Metered Areas (DMAs), and an increase in the number of customers by at least 20,750 households (representing a 22% increase from 2023).